Peach Blossom Shangri-la: Tao Hua Yuan Ji - Tao, Qian, 372?-427 (Salt Lake City, UT : Project Gutenberg, 2000)
"Peach Blossom Shangri-la: Tao Hua Yuan Ji" by Tao Yuan Ming is a notable classic of Chinese literature, categorized as a narrative prose written during the early 5th century AD. This timeless tale delves into themes of escapism and the search for an idyllic utopia, reflecting on the contrast between the chaotic outside world and the serene haven found within the peach blossom grove. The story follows a humble fisherman who, while venturing along a stream, stumbles upon a hidden paradise filled with beautiful peach trees and welcoming villagers who have lived in isolation since the tumult of the Qin Dynasty. The villagers, untouched by the outside world's chaos, express their blissful ignorance of contemporary dynasties, fostering a profound connection with the fisherman. After spending a few days in this utopia, he leaves, eager to share this paradise with others, but upon returning to the prefecture, his attempts to re-find the place are futile, as no one is able to trace his path. Ultimately, this tale embodies a longing for peace and contentment away from the complexities of life and explores the ephemeral nature of such escapes. (This is an automatically generated summary.)
Release date is 2000-02-01
Produced by Rick Davis and David Steelman
Keywords: Chinese literature -- Translations into English; Chinese fiction -- To 618